Long Intergenic Non-Coding 00162 as Diagnostic Biomarker for Early-Stage Pancreatic Cancer - Chen, Mingxing; Lu, Yu; Qin, Simeng; Hu, Zuojian; Chen, Huaping; Lu, Liuyi; Mo, Cuiju; Zhang, Xiaolian; Huang, Junhui; Qin, Xue (Annals of clinical and laboratory science, 2022)
Pancreatic cancer (PC) is the fourth leading cause of cancer death due to insufficient diagnostic methods in early stage of PC. Growing evidence has shown that long intergenic non-coding RNAs (LINCRNAs) is a biomarker of the early-stage of PC. However, the expression level and diagnostic value of LINC00162 remains unclear. LINC00162 expression was detected in peripheral blood samples from 155 subjects (52 healthy controls, 52 benign pancreatic disease (BPD) persons and 51 PC patients) by quantitative reverse transcription real-time polymerase chain reaction. Receiver operating characteristic (ROC) analysis was used to evaluate the diagnostic value of LINC00162, carcinoembryonic antigen (CEA) and cancer antigen 199 (CA199). Our data indicated that the LINC00162 expression was upregulated in PC patients compared with healthy controls and BPD (all <0.001). Furthermore, PC patients with advanced pathological grades, positive lymph node metastasis and positive distant metastasis showed higher LINC00162 levels (all <0.001). In addition, the area under the ROC curve (AUC) found that the LINC00162 had higher diagnostic ability than CEA and CA199 in distinguishing the early-stage PC patients (AUC: LINC00162 versus(vs) CEA vs CA199=0.932 vs 0.669 vs 0.725). In summary, the LINC00162 may be a noninvasive and efficient marker for identifying patients with the early-stage PC. Further validation studies with a large number of patients and long-term follow-up patients are needed to confirm the potential diagnostic value and clinical utility of LINC00162 in patients with PC.